A national quality assurance programme for point-of- care testing in Malawi - Lutho I. Zungu; Termson Magombo; Tarsizio Chikaonda; Rachel Thomas; Reuben Mwenda; James Kandulu; Benson Chilima; Mavuto Chiwaula; Alwin Mbene; Emmanuel Saka (AOSIS, 2016)
No abstract available.